P719Different regulation of vascular NOX-1 and NOX-4 expression by interleukin-1beta and angiotensin II. (15th July 2014) - Aguado Martinez, A; Zhenyukh, O; Fischer, T; Rodriguez, C; Martinez, J; Martinez Revelles, S; Aras, R; Dixon, D; Briones, A M; Salaices, M
Abstract: Purpose. The NADPH oxidase (NOX) is the main source of reactive oxygen species (ROS) which are important in vascular remodeling. Interleukin 1b (IL-1β) and angiotensin II (Ang II) induce different NOX isoforms. We assessed the effects of IL-1β and Ang II on NOX-1 and NOX-4 expression, NOX activity and ROS production, the mechanisms involved and their functional role. Methods. Rat and human aortic smooth muscle cells were stimulated with with IL-1b or Ang II+IL-1b (4, 8 or 24 h). mRNA level was measured by qPCR. NOX-1 and NOX-4 promoter and 3'UTR activity were measured by luciferase assay. HuR cytoplasmic translocation was measured by immunofluorescence and cellular fractionation and the HuR binding to NOX-1 mRNA by immunoprecipitation. NOX activity and ROS production were measured by lucigenin chemiluminescence and with dihydroethidium staining, respectively. Cell proliferation was analyzed by a commercial kit and cell migration by wound healing and transwell. Results. IL-1b (10 ng/ml) increased NOX-1 expression, NOX activity and ROS production, and decreased NOX-4 expression. Ang II (0.1 μM) potentiated NOX-1 expression, NOX activity and ROS production induced by IL-1b and it did not modify IL-1b-induced NOX-4 downregulation. The potentiation of NOX-1 was reduced by ERK1/2, p38MAPK and JNK inhibitors and was accompanied by an increase of mRNA stability. These effects were also inhibited by a HuR inhibitor. Ang II+IL-1b promoted HuR translocation to the cytoplasm and its binding to NOX-1 mRNA. A NOX-1 inhibitor blocked the Ang II+IL-1b-induced cell migration but it did not affect cell proliferation. The decrease of NOX-4 expression induced by IL-1b was blocked by ERK1/2, JNK and PI3K inhibitors and was accompanied by a decrease in the 200 bp proximal promoter activity. These effects were inhibited by cycloheximide. Histone deacetylase inhibitors decreased the basal 200 bp NOX-4 promoter activity and NOX-4 mRNA expression. Conclusions. 1) Ang II potentiates IL-1b-induced vascular expression of NOX-1 through an increase of mRNA stability mediated by HuR. 2) NOX-1-derived-ROS participate in Ang II+IL-1b-induced cell migration. 3) IL-1b induced NOX-4 downregulation mediated by an inducible repressor which binds to the 200 bp proximal promoter. 4) Basal NOX-4 expression depends on deacetylation of a transcription factor that binds to NOX-4 200 bp proximal promoter. 5) An unbalance between NOX-1 and NOX-4 in inflammatory conditions might contribute to vascular remodeling.